Acoustical Boundary Elements: Theory and Virtual Experiments - PISCOYA, Rafael; OCHMANN, Martin (Archives of Acoustics, 2014)
This paper presents an overview of basic concepts, features and difficulties of the boundary element method (BEM) and examples of its application to exterior and interior problems. The basic concepts of the BEM are explained firstly, and different methods for treating the non-uniqueness problem are described. The application of the BEM to half-space problems is feasible by considering a Green’s Function that satisfies the boundary condition on the infinite plane. As a special interior problem, the sound field in an ultrasonic homogenizer is computed. A combination of the BEM and the finite element method (FEM) for treating the problem of acoustic-structure interaction is also described. Finally, variants of the BEM are presented, which can be applied to problems arising in flow acoustics.